SPIRITUAL LEADERSHIP DALAM PROSES BELAJAR MENGAJAR: Spiritual Leadership In Teaching And Learning - Faisol Abrari (LP2M UIN KH.Achmad Siddiq Jember, 2019)
Educational institutions and Spiritual institutions cannot be sterile from the disruption era. A good learning process needs a good relationship between teachers and students. A good learning process needs high motivation, and the teachers must have an excellent motivating ability. Teachers must implement spiritual leadership in learning. The soul of peace, tranquility, sincerity, compassion, and perfection will influence the learning process.